2021
DOI: 10.1590/1413-81232021267.07252021
|View full text |Cite
|
Sign up to set email alerts
|

Violências nas trajetórias afetivo-sexuais de jovens gays: “novas” configurações e “velhos” desafios

Abstract: Resumo Este artigo aborda o fenômeno da violência nas trajetórias afetivo-sexuais de jovens gays cisgênero, pertencentes a camadas populares da região metropolitana do Rio de Janeiro, Brasil. A literatura brasileira sobre violência contra homens gays, geralmente, tem como foco a discriminação sofrida por esta população, mas pouco se problematiza a violência que eles sofrem nas relações familiares devido à sua orientação sexual, ou ainda, em suas relações ditas como “namoro” ou “ficar”. Com o objetivo de discut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
6
Order By: Relevance
“…Bottoms often feel more submissive and vulnerable during anal intercourse (Ravenhill & de Visser, 2018 ). It has also been suggested that some men practise stealthing with the belief that they have the right to ‘spread their seed’ because of sexual supremacy (Ebrahim, 2019 ; Ferrari et al, 2021 ). Studies among Chinese MSM also proposed that some Chinese tops may have a more active and dominant role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bottoms often feel more submissive and vulnerable during anal intercourse (Ravenhill & de Visser, 2018 ). It has also been suggested that some men practise stealthing with the belief that they have the right to ‘spread their seed’ because of sexual supremacy (Ebrahim, 2019 ; Ferrari et al, 2021 ). Studies among Chinese MSM also proposed that some Chinese tops may have a more active and dominant role.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that stigma causes MSM to defer health service utilization for HIV‐related health concerns or prevention (Mo et al, 2018 ), and an integrative review reported that sexual minority people experienced a nexus of exclusion and oppressive social norms when they received nursing services (Nhamo‐Murire & Macleod, 2018 ). A recent study in Brazil found that MSM encountered unfavourable experiences when they wanted to obtain PEP (Ferrari et al, 2021 ). The nurses were judgmental and disrespectful because of their sexual orientation (Ferrari et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além do mais, a homofobia vivenciada no atendimento que essas pessoas recebem também tem impacto na decisão de não procurar ajuda formal e, assim, HRH podem se sentir menos motivados para procurar ajuda do Estado em situações de VPI, pois as relações homossexuais não são bem-vistas na sociedade brasileira, o que pode causar diversas formas de revitimização dessas pessoas. De acordo com Ferrari et al (2021), jovens gays que sofreram VPI de seus parceiros não os denunciaram pelo medo de serem discriminados nas delegacias, o que limitou suas redes de apoio.…”
Section: Denúncia No Estadounclassified
“…Como escrevem Ferrari et al (2021), tais práticas perpassam relações hierárquicas fundadas em normas heterossexuais, em ideias como o 'estupro corretivo' ou do 'possível' consentimento da vítima, em virtude de sua orientação sexual, "Já outros dois jovens, EF23 e RT22, se consideravam "muito afeminados desde criancinhas". Em comum, nota-se uma mesma frase dita pelos agressores: "Você é viadinho, tem que aprender a virar homem"; "Você é viadinho, vai acabar gostando (do abuso)"."…”
Section: Plíniounclassified